Cryptosporidium spp. in Dogs - Prevalence and Genotype Distribution - Çelik, Özgür Yaşar; Akın Koçhan; Burçak Aslan Çelik; Adnan Ayan; Gürkan Akyildiz; Özlem Orunç Kilinç; Kerem Ercan; Vedat Baldaz; Özge Oktay Ayan (Acta Scientiae Veterinariae, 2023)
Background: Cryptosporidium spp. is a zoonotic protozoan parasite that affects the gastrointestinal tract of humans and animals. The disease can cause acute and chronic diarrhoea and even death in both humans and animals. In this study, it was aimed to determine the prevalence and genotype distribution of Cryptosporidiosis in shelter dogs in Diyarbakır province located in the Southeastern Anatolia Region of Turkey. Materials, Methods & Results: The animal material of the study consisted of 100 dogs of different breeds and sexes. Faecal samples were collected from the rectum with disposable latex gloves and placed in individual sample containers. All of the samples were examined for Cryptosporidium spp. by Kinyoun Acid Fast and Nested PCR methods. In the Kinyoun Acid Fast staining method, firstly, smear preparations were prepared from fresh faecal samples, fixed in pure methanol for 1 min and allowed to dry. The slides were kept in Kinyoun Carbol-Fuxin for 5 min, dipped in 50% ethyl alcohol, shaken, washed in tap water, kept in 1% sulphuric acid for 2 min and washed in tap water. The slides were kept in methylene blue for 1 min, washed in tap water and allowed to dry. After drying, immersion oil was dripped and examined under a microscope at 100 magnification. DNA extraction was performed from all samples using GeneMATRIX Stool DNA Purification Kit according to the manufacturer’s protocol. After Nested PCR analysis was performed. In the PCR step, primers 5’-TTCTAGAGCTAATACATGCG-3’ and 5’- CCCATTTCCTTCCTTCGAAACAGGA-3’ were used to amplify the 1325 bp gene region. In the nested PCR step, primers 5’- GGAAGGGTTGTATTTATTTATTAGATAAAG-3’ and 5’-AAGGAGTAAGGAACAACCTCCA-3’ were used to amplify the 826-864 bp gene region. As a result of both methods, a prevalence of 3% was determined. The infection rate was higher in males (3.57%) than females (2.27%) and in younger than 1 year (5.56%) than in older than 1 year (1.56%). The DNA sequences obtained from the sequence analysis of 3 positive PCR samples were analysed in BioEdit software. A phylogenetic tree was constructed with the data set created by using the 18s rRNA gene sequences obtained from the NCBI genbank database and the DNA sequences obtained as a result of the study, and it was shown which Cryptosporidium species the study samples were related to. Today, many Cryptosporidium species have been identified and most of these species have host adaptation. Although C. canis is the most common species in dogs, C. muris, C. meleagridis, and C. parvum have also been detected. Among these species, C. parvum is recognized as a zoonotic species infecting a wide range of mammals. In this study, DNA sequencing of nested PCR positive samples revealed that 3 samples were zoonotic C. parvum. Discussion: This suggests that dogs may be a reservoir for zoonotic transmission of Cryptosporidium. Consequently, it is recommended that people should be informed about the potential for transmission of this protozoan to humans and animals and that control programmes should be implemented, including the prevention of free entry of stray dogs into public places and homes. Keywords: Cryptosporidium parvum, molecular analysis, canine, Diyarbakır, Turkey.